Das Bild der Stadt. 8., unveränd. Nachdruck der 2. Aufl. 2013. - Lynch, Kevin (Bauverl., 2017)
Wie orientieren wir uns in einer Stadt? Woher rühren unsere ganz fest umrissenen visuellen Vorstellungen? Um diese Fragen beantworten zu können, studierte der Autor die Erfahrungen von Menschen und zeigt damit, wie man das Bild der Stadt wieder lebendiger und einprägsamer machen könnte.

Urbanization is transforming the planet, within and beyond cities, at all spatial scales. In this book, Neil Brenner mobilizes the tools of critical urban theory to deconstruct some of the dominant urban discourses of our time, which naturalize, and thus depoliticize, the enclosures, exclusions, injustices and irrationalities of neoliberal urbanism. In so doing, Brenner advocates a constant reinvention of the framing categories, methods and assumptions of critical urban theory in relation to the rapidly mutating geographies of capitalist urbanization. Only a theory that is dynamic-which is constantly being transformed in relation to the restlessly evolving social worlds and territorial landscapes it aspires to grasp-can be a genuinely critical theory.
Keywords: Stadtstruktur; Stadtbild; Stadtgestaltung; Architektur; Orientierung